Implementation of Therapeutic Virtual Reality Into Psychiatric Care: Clinicians' and Service Managers' Perspectives - Chung, Olivia S.; Robinson, Tracy; Johnson, Alisha M.; Dowling, Nathan L.; Ng, Chee H.; Yücel, Murat; Segrave, Rebecca A. (Frontiers in Psychiatry, 2022)
Objectives: Virtual reality (VR) has emerged as a highly promising tool for assessing and treating a range of mental illnesses. However, little is known about the perspectives of key stakeholders in mental healthcare, whose support will be critical for its successful implementation into routine clinical practise. This study aimed to explore the perspectives of staff working in the private mental health sector around the use of therapeutic VR, including potential implementation barriers and facilitators. Methods: Semi-structured qualitative interviews were conducted with cross-disciplinary clinicians (n = 14) and service managers (n = 5), aged 28–70 years working in a major private mental health hospital in Victoria, Australia. Transcripts were analysed using general inductive coding to allow themes to naturally emerge. Results: Three major themes were identified: clinical factors (four subthemes), organisational factors (five subthemes), and professional factors (three subthemes). The themes encompassed enabling factors and potential barriers that need to be addressed for successful implementation of VR. Clinical factors highlighted the influence of knowledge or perceptions about appropriate clinical applications, therapeutic efficacy, safety and ethical concerns, and patient engagement. Organisational factors emphasised the importance of service contexts, including having a strong business case, stakeholder planning, recruitment of local opinion leaders to champion change, and an understanding of resourcing challenges. Professional factors highlighted the need for education and training for staff, and the influence of staff attitudes towards technology and perceived usability of VR. Conclusions: In addition to enabling factors, potential implementation barriers of therapeutic VR were identified, including resourcing constraints, safety and ethical concerns, negative staff attitudes towards technology and VR system limitations. Future dissemination should focus on addressing knowledge and skills gaps and attitudinal barriers through development of clinical guidelines, training programs, and implementation resources (e.g., adoption decision tools, consultation opportunities).